ANALISIS PERBANDINGAN PRAKTIK AKUNTANSI MUDHARABAH DAN MUSYARAKAH DENGAN PSAK 105 DAN 106 DI PERBANKAN SYARIAH - Aldi Susanto; Lutfiyaumul Latifah; Padilatul Laila; Istiqomah -; Nur Alfu Laila (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2024)
Sharia banking is a financial institution that has sharia principles andapplies Islamic law in making decisions. In the form of fund distribution can beaccessed by mudharabah and musyarakah financing, in terms of the concept ofmudharabah and musharakah has the principle of trust (trust) but in practiceIslamic banks apply guarantees in their financing, this is not in accordance with theinitial principle of mudharabah and musharakah, namely the trust system. Thepurpose of this research is to find out the difference between mudharabah andmusharakah in Islamic banking and to find out the application of guarantees inIslamic banking. This type of research uses a library research approach. With theprimary data source is the book